Leukoaraiosis and Gray Matter Volume Alteration in Older Adults: The PROOF Study - Celle, Sébastien; Boutet, Claire; Annweiler, Cédric; Ceresetti, Romain; Pichot, Vincent; Barthélémy, Jean-Claude; Roche, Frédéric (Frontiers in Neuroscience, 2022)
Background and Purpose: Leukoaraiosis, also called white matter hyperintensities (WMH), is frequently encountered in the brain of older adults. During ageing, grey matter structure is also highly affected. WMH or grey matter defects are commonly associated with a higher prevalence of mild cognitive impairment. However, little is known about the relationship between WMH and grey matter. Our aim was thus to explore the relationship between leukoaraiosis severity and grey matter volume in a cohort of healthy older adults. Methods: Leukoaraiosis was rated in participants from the PROOF cohort using the Fazekas scale. Voxel-based morphometry was performed on brain scans to examine the potential link between WMH and changes of local brain volume. A neuropsychological evaluation including attentional, executive, and memory tests was also performed to explore cognition. Results: Out of 315 75-years-old subjects, 228 had punctuate foci of leukaraiosis and 62 had begun the confluence of foci. Leukoaraiosis was associated with a decrease of grey matter in the middle temporal gyrus,in the right medial frontal gyrus and in the left parahippocampal gyrus. It was also associated with decrease performances in memory recall, executive functioning and depression. Conclusions: In a population of healthy older adults, leukoaraiosis was associated with grey matter defects and reduced cognitive performance. Controlling vascular risk factors and detecting early cerebrovascular disease may prevent, at least in part, dementia onset and progression.